Implications of Cation Interdiffusion between Double Perovskite Cathode and Proton-Conducting Electrolyte for Performance of Solid Oxide Fuel Cells - Nadezhda S. Tsvetkova; Dmitry A. Malyshkin; Ivan L. Ivanov; Dmitry S. Tsvetkov; Andrey Yu. Zuev (Energies, 2023)
Chemical compatibility and cation interdiffusion between the double perovskite cobaltites RBaCo2O6−δ (R = Gd, Pr) and proton-conducting electrolyte BaZr0.8Y0.2O3−δ were studied. Chemical interaction was found to occur already at 1100 °C as a result of the partial dissolution of RBaCo2O6−δ (R = Gd, Pr) in BaZr0.8Y0.2O3−δ. Analysis of the element distribution along the cross sections of diffusion couples RBaCo2O6−δ(R = Gd, Pr)|BaZr0.8Y0.2O3−δ showed strong interdiffusion of cations, with cobalt being the most mobile one. Its diffusion depth in the electrolyte reaches up to several hundreds of micrometers. The addition of NiO as a sintering aid to BaZr0.8Y0.2O3−δ promotes cation diffusion especially through the grain boundary mechanism, increasing the diffusion depth of Co. The possible implications of cation interdiffusion on the performance of proton-conducting SOFCs are discussed based on the results obtained.